Heat-treated 3, 5-diamino-1, 2, 4-triazole/graphene hybrid functions as an oxygen reduction electrocatalyst with high activity and stability. (20th October 2015) - Koshikawa, Hiroyuki; Nakanishi, Shuji; Hashimoto, Kazuhito; Kamiya, Kazuhide
Graphical abstract: Highlights: The mixture of reduced graphene oxides and Cu-DAT was heat treated at 900 °C for 45 s. N atoms coordinated to Cu atoms were doped into graphene through the heat treatment. The resulting catalyst exhibited the efficient ORR activity in neutral solutions. The onset potential (790mV vs RHE) is the highest among Cu based electrocatalysts. The stability of the catalyst was enhanced by the heat treatment. Abstract: We synthesized a novel copper-based oxygen reduction electrocatalyst by heat treating a mixture of reduced graphene oxides and a copper complex of 3, 5-diamino-1, 2, 4-triazole at 900 °C for only 45 s. Extended X-ray absorption fine structure and X-ray photoelectron spectroscopy analyses of the synthesized catalyst revealed that the nitrogen (N) atoms coordinated to copper (Cu) atoms were doped into the sp2 networks of graphene. In neutral solutions, the catalyst exhibited efficient electrocatalytic activity for oxygen reduction, with an onset potential of 790 mV. More importantly, the catalyst possesses high stability due to the anchoring of active Cu-sites into the graphene substrate via the Cu-N coordination bonds.